1966
DOI: 10.1177/030098586600300104
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Findings in Swine Affected with a Virulent Strain of Aujeszky's Virus

Abstract: The histopathology of Aujeszky's disease associated with severe clinical signs in mature swine was studied in 46 naturally and experimentally infected pigs, 2 dogs, a sheep, and 5 experimentally infected rabbits. The lesions in swine were characteristically severe, non-suppurative, necrotizing panencephalomyelitis, meningitis, and ganglioneuritis. In naturally infected pigs the anterior regions of the CNS were most severely involved. Swine experimentally inoculated intranasally had a similar distribution of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 4 publications
2
25
0
1
Order By: Relevance
“…In this respect, it is important to note that the 15-week-old pig that spontaneously died at day 5 p.i., N09, and the one that was euthanized due to the severe neurological symptoms at day 6 p.i., N10, were among those with the highest IFN-␥ expression in the olfactory bulb. As such, our data suggest that infection of the olfactory bulb may play a significant role in severe PRV pathology and add to previous findings showing the importance of the olfactory bulb for neuropathogenesis and invasion of the CNS (7,14,15).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this respect, it is important to note that the 15-week-old pig that spontaneously died at day 5 p.i., N09, and the one that was euthanized due to the severe neurological symptoms at day 6 p.i., N10, were among those with the highest IFN-␥ expression in the olfactory bulb. As such, our data suggest that infection of the olfactory bulb may play a significant role in severe PRV pathology and add to previous findings showing the importance of the olfactory bulb for neuropathogenesis and invasion of the CNS (7,14,15).…”
Section: Discussionsupporting
confidence: 86%
“…Viral replication at the respiratory mucosa is likely required before dissemination of PRV to the visceral organs, since virus only reached the organs several days after infection. Our results also confirmed the importance of the olfactory route as an alternative route of neuroinvasion (7,14,15). Despite the confirmation of the general knowledge on PRV pathogenesis, several interesting new findings resulted from the detailed study of viral and cytokine mRNA expression at important sites of neuropathogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…In-vivo experiments suggest that herpes viruses migrate from the inoculation site along peripheral nerves towards the associated peripheral ganglia, and then proceed to the corresponding segments of the CNS (Irie et al, 1989). In ADV infection in piglets, necrotizing enteritis and myenteric plexitis occur (Narita et al, 1984;Ezura et al, 1995) in addition to encephalitis (Olander et al, 1966;Rajcani et al, 1969;Sabo et al, 1969). The neuronal lesions produced in the present study suggested that ADV spread from the myenteric plexuses via the solar plexus and ganglia, and travelled to the spinal ganglia as far as the dorsal and ventral horns of the thoracic-lumbar spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Aujeszky's disease virus (ADV), a neurotropic herpesvirus, spreads via the nerves from the primary site of infection to the central nervous system (CNS) (Corner, 1965;McFerran and Dow, 1965;Bergmann and Becker, 1967;Rajcani el al., 1969;Sabo et al, 1969;Narita et al, 1991). In piglets, initial replication of ADV in the naso-pharyngeal mucosa and tonsillar epithelium leads to systemic infection with necrotic hepatitis, adrenitis and encephalitis (Corner, 1965;McFerran and Dow, 1965;Olander et al, 1966). Recent studies showed that some strains of ADV produce necrotic lesions in the gastrointestinal tract and myenteric plexuses (Narita et al, 1984(Narita et al, , 1998Ezura et al, 1995;Zhao et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, microscopic findings may include necrotic tonsilitis, bronchitis, bronchiolitis, alveolitis. Intranuclear inclusion bodies are observed in neurons, astrocytes and Oligodendroglia (Dow and McFerran 1962, Csontos and Szeky 1966, Olander et al 1966, Baskerville 1972a, b, 1973. Focal necrotic areas may, also, be found in the liver, spleen, lymph nodes and adrenal glands of macerated fetuses.…”
Section: Lesionsmentioning
confidence: 99%